2022
DOI: 10.1186/s13643-022-02125-w
|View full text |Cite
|
Sign up to set email alerts
|

The teaching and learning of communication skills for social work students: a realist synthesis protocol

Abstract: Background Good interpersonal communication is the cornerstone of social work practice, enhancing the outcomes of people in receipt of its services. Social workers’ communication skills are often identified as an area of concern. Communication skills can be developed and refined through training or education. The teaching and learning of communication skills is firmly embedded in many social work qualifying courses; however, considerable heterogeneity exists regarding such complex interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Realist synthesis is an interpretive theory‐driven methodological approach to reviewing quantitative, qualitative and mixed methods research evidence about complex social interventions to provide an explanatory analysis of how and why they work in particular contexts or settings. This research approach would support the theoretical development of the teaching and learning of communication skills in social work education, complementing that of this systematic review (Reith‐Hall, 2022).…”
Section: Authors’ Conclusionmentioning
confidence: 81%
“…Realist synthesis is an interpretive theory‐driven methodological approach to reviewing quantitative, qualitative and mixed methods research evidence about complex social interventions to provide an explanatory analysis of how and why they work in particular contexts or settings. This research approach would support the theoretical development of the teaching and learning of communication skills in social work education, complementing that of this systematic review (Reith‐Hall, 2022).…”
Section: Authors’ Conclusionmentioning
confidence: 81%
“…The level of education was measured against the other two variables because it was constant given that the main object of the study is to determine the effect of education level on communication skills and, hence, employability. Some studies mentioned in the literature review found that enhanced communication skills can positively influence an individual's personality, academic achievement, and career outcome (Reith-Hall, 2022;Sabbah et al, 2020). The results show that the level of education has a significant association with monthly income and age group but not the work sector.…”
Section: Chi-square Analysismentioning
confidence: 88%
“…(2022) also found that relationships among college students influenced their academic outcomes greatly, especially when exchanging ideas and experiences. Moreover, enhanced communication skills can positively affect the student's personality and academic achievement (Reith-Hall, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Estas habilidades suponen la superación de la individualidad y de acuerdo con Reith-Hall (2022) se configuran como la piedra angular de la práctica del trabajo colaborativo. Para Fatmaryanti et al, (2022) Ante este panorama, es evidente que el modelo educativo de EaD actual, no está comprometido con la promoción del aprendizaje a partir de las interacciones colaborativas de los estudiantes, así pues, no tiene normado con claridad cómo debe hacerse el trabajo coordinado entre pares, cómo se deben distribuir las tareas y roles, entre otros aspectos que garanticen la efectividad del trabajo colaborativo como estrategia didáctica (Acosta et al, 2020).…”
Section: Introductionunclassified